Application Of The Business Judgment Rule Doctrine To Business Decisions Of The Directors Of The State-Owned Enterprise Persero As A Legal Entity Whose Capital Comes From Separated State Assets - Laksemini, Wayan; Sihotang, Erikson; Ketut Wiratny, Ni (International Journal of Educational Research & Social Sciences, 2024)
The juridical basis for the application of the business judgment rule principle is a reflection ofthe independence and discretion of the board of directors, where in every decision they make, noparty should be able to interfere with the challenge of their decision, including the court, even iftheir decision causes the company to suffer losses. This is regulated in Article 97 paragraph (5)and Article 104 paragraph (4) of Law no. 40 of 2007 concerning Limited Liability Companies.This provision also applies to State-Owned Enterprises Persero based on Article 1 point 2,Article 11, Article 91 of Law no. 19 of 2003. Apart from that, the Supreme Court has also issuedSupreme Court Fatwa Number WKMA/Yud/20/VIII/2006 which confirms that state assets thathave been separated into BUMN are not state assets and that all provisions and principles applyto BUMN Persero. the principles of limited liability companies regulated in Law no. 40 of 2007concerning Limited Liability Companies. The principles of business judgment rules are applied tothe directors of State-Owned Enterprises Persero if they make business decisions in accordancewith applicable law, namely; Done in good faith, done with the right aim (prosper purpose), thedecision has a rational basis (rational basis), done with due care as would be done by a personwho is careful enough in a similar position, and carried out in a manner that he reasonablybelieves is in the best interest for the company.